Synchronized nutrition fertilizer improves soil microbial diversity and sugarcane yield through agrochemical and enzymatic regulation - Qi, Xiuxiu; Jiang, Jiaquan; Yang, Di; Li, Qingbo; Gao, Chengxiang; Zhang, Lidan; Sun, Shaolong; Fan, Xiaolin (Frontiers in Plant Science, 2025)
IntroductionThe new type of synchronized nutrition fertilizers (SNFert) has been popularized and applied in agro-production in northern China. However, the impacts of the SNFert on soil microbial diversity and sugarcane growth have not yet been thoroughly investigated.MethodsTo clarify the influences of SNFert on soil properties, sugarcane yield, soil microbial diversity and their interactions, two years of field experiments with four treatments, including CK, non fertilizer; CF, conventional chemical fertilizer; SNF1, 15% less fertilizer applied than CF; SNF2, 25% less than CF, were conducted.ResultsResults showed that yield, °Brix in the SNFert, even with 15% and 25% less fertilizer input, were no significant differences with those of CF. Specifically, SNF1 increased sugarcane yield and tillers by 6.84% and 18.63%, raised pH and urease by 0.40 units and 2.29 times, reduced Nmin and EC by 81.69% and 77.69% with 15% lower fertilizer input, respectively. In 2020, soil microbial diversity was enriched by SNFert through regulating microbial communities and functions. As a new kind of chemical fertilizer, SNF1 overcame the shortcomings of CF in reducing the soil microbial diversity, that was, there were no statistically differences in microbial alpha diversity indices between SNF1 and CK. The abundance of beneficial functional taxa Chloroflexi, Proteobacteria, Acidobacteriota in bacteria and Mortierellomycota in fungi of SNF1 increased by 12.46%, 15.64%, 47.63% and 164.00%, respectively. The soil carbon and nitrogen cycle was driven by those taxa. The plant-microbe nutritional exchanges were then improved. In mechanism, SNFert not only supplemented nutrients, but also enriched soil microbial diversity by increasing soil pH and decreasing soil salinity and mineral nutrient residues, thereby improving soil properties and increasing sugarcane yield in 2020.DiscussionIn conclusion, replacing CF with SNFert in sugarcane cultivation is an effective fertilization measure to reduce the dosage of CF, optimize soil agrochemical properties, and increase soil microbial diversity.